Simulation and experimental analysis on automotive radiator using organic nanocellulose - Ihsan Naiman, Ibrahim (2022)
All the excessive heat obtained in an internal combustion engine is removed by the automotive cooling system to avoid any overheating. Furthermore, a literature survey showed that improvement on the fins and microchannel in the radiator already reached its limitation. Besides that, it has been known that the conventional thermal transport fluid has a low thermophysical property and results in poor heat dissipation from the engine. Demand for thermal transport fluid with high thermophysical property is increasing as it is able to enhance heat transfer performance. In addition, after using the improved thermal transport fluid, the size of the radiator can be minimised which also reduces the weight of the vehicle. Moreover, it helps to improve the engine performance of any vehicle. A few decades ago, nanofluid was widely researched to be used in heat transport applications. Nanofluid is prepared by dispersing nano-scaled materials into a base fluid which enhances the thermophysical property of the fluid. In this research, the nanosubstance used was nanocellulose that had been extracted from a Western Hemlock plant at a weight concentration of 8.0%, to be used as a novel thermal transport fluid in the radiator. The nanosubstance is dispersed into the ethylene glycol-distilled water mixture at a volume ratio of the 40:60, respectively. The heat transfer performance ofthe nanofluid and conventional ethylene glycol-water mixture iscompared in a fabricated radiator test rig. Then, the experiment was conducted to validate with experiment of a radiator with nanofluid dispersed in Ethylene Glycol and water at different ratios. The nanofluid is prepared by using a two-step preparation method. The stability of nanofluid is evaluated through qualitative and quantitative method. The stability results proved that nanofluid can be stable for more than a month. The thermophysical property measurement for nanofluid is measured for volume concentration of 0.5%, at a temperature range from 30 oC to 80 oC. Analysis from a statistical tool showed that volume concentration of 0.5% has an optimised thermophysical property and it had been used as nanofluid (thermal transport fluid) in any radiator. An experiment for heat transfer performance of nanofluid and conventional thermal transport fluid was conducted in the automotive radiator test rig. The experiment was conducted under two different circumstances: without the influence of draft fan and with the influence of draft fan. The experiment results showed that experimental heat transfer coefficient, convective heat transfer, Reynolds number, Nusselt number had a proportional relation to the volumetric flow rate. Meanwhile, friction factor had an inverse relation to the volumetric flow rate. Without the influence of fan, the maximum convective heat transfer enhancement recorded was 66.85% and with the influence of fan, it was at 55.27%. Thus, the nanofluid was able to remove heat efficiently from any automotive cooling system. On the other hand, maximum heat transfer enhancement involving the ratio of convective heat transfer to conductive heat transfer in radiator is 39.75% without the influence of draft fan circumstance and 43 .24% with the influence of fan circumstance. Besides that, maximum thermal and hydraulic performance factor without and with the influence of fan is 2.15 and 2.28, respectively. Thus, nanocellulose based nanofluid is suitable for automotive cooling application since it has a better heat transfer performance than conventional thermal transport fluid.